Treatment with Pueraria mirifica extract prevented muscle atrophy and restored muscle strength in ovariectomized rats - Kochakorn Sukjan Inthanuchit,; Wandee Udomuksorn,; Ekkasit Kumarnsit,; Surapong Vongvatcharanon,; Uraporn Vongvatcharanon, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Pueraria mirifica (PM) is a phytoestrogen-rich plant that was tested to establish if its phytosteroids could prevent estrogen dependent sarcopenia. The effect of PM on the estrogen levels, estrous cycle, toxicity, muscle mass, strength and endurance of extensor digitorum longus (EDL) and gastrocnemius muscles of ovariectomized rats was investigated. Adult female Wistar rats were divided into six groups: Sham-operated (SHAM); ovariectomized (OVX) fed with distilled water (PM0); OVX injected with 40 μg/kg estradiol benzoate (E40); (4-6) OVX fed with ethanolic extract of PM at doses of 50 (PM50), 500 (PM500) and 1000 (PM1000) mg/kg for 90 days. After treatment with all three doses of PM, no toxicity was detected to the hematopoietic system and liver function whereas the E40 group did show toxic effects. Treatment with 50 and 500 mg/kg of PM showed no effect on uterine hypertrophy and caused no arrest of the estrous cycle whereas treatment with estrogen and 1000 mg/kg of PM treatment did. The estrogen level, the cross sectional area of the EDL and the gastrocnemius muscle fiber strength and endurance were all significantly reduced in the PM0 group compared to that of the SHAM group (p<0.05) but were significantly increased in the E40, PM50, PM500 and PM1000 compared to that of the PM0 group (p<0.05). This indicated that the estrogenic activity of PM alleviated muscle atrophy and built up muscle strength and endurance. Thus, the 50 and 500 mg/kg of PM were suitable for treating estrogen dependent sarcopenia in ovariectomized rats.